Multi-omics approaches reveal the mechanisms underlying the interaction between cyst fluid of Echinococcus granulosus and host immune cells - He, Rongdong; Yan, Ruofeng; Shi, Yuanchun; Aierken, Aili; Zhang, Xue; Wen, Hao; Aimulajiang, Kalibixiati (Frontiers in Immunology, 2025)
BackgroundEchinococcus granulosus cyst fluid (EgCF) is a complex mixture of parasite’s containing a variety of antigens. Th9 cells are a newly reported subpopulation of Th cells whose primary function is to secrete IL-9 and exert biological effects. Research on whether antigens in the vesicle fluid can evade the host immune response by increasing IL-9 secretion is limited.MethodsThe effects of EgCF on lymphocyte function in mice were evaluated using CCK-8 and flow cytometry for apoptosis. The effect of EgCF on CD4+IL-9+T cell differentiation was reflected by flow cytometry. The expression of TGF-β, IL-4, PU.1, IRF4 and IL-9 was detected by WB, qRT-PCR and ELISA under the influence of varying concentrations of EgCF. Analysis of differential metabolites and genes in mouse splenic lymphocytes was stimulated by EgCF using metabolomics and transcriptomics.ResultsDifferent concentrations of EgCF stimulated lymphocytes, promoted cell proliferation and apoptosis, facilitated the differentiation of CD3+T cells and CD4+IL-9+T cells in splenic lymphocytes, and inhibited the differentiation of CD4+T cells. It regulated the host immune response by up-regulating Th9 cell-associated cytokines such as IL-4, TGF-β, IL-9 and related transcription factors PU.1 and IRF4. Metabolomic analysis identified 221 differential metabolites, 12 up-regulated and 11 down-regulated. These metabolites were primarily enriched in metabolic pathways such as beta-Alanine metabolism and Pyrimidine metabolism. Transcriptome analysis identified 16,694 differentially expressed genes, highlighting necroptosis and TGF-β signaling as top pathways, where Hgf and Myof were potential diagnostic markers.ConclusionsMetabolomics and transcriptomics analyses help identify potential candidate genes and provide diagnostic tools for future research and the discovery of new therapeutic targets. EgCF may regulates the host immune response by up-regulating Th9 cell-related cytokines such as IL-4, TGF-β and IL-9, along with related transcription factors PU.1 and IRF4. This provides a theoretical basis for understanding how Echinococcus granulosus modulates the host immune response and may offer new research avenues for immunoprophylaxis against Echinococcus granulosus.